PSO Based Model Reference Adaptive PI Controller for a Conical Tank Level Process - Raghuraman, R.; Senthilkumar, M. (Asian Journal of Electrical Sciences, 2019)
Conical tanks are mostly used in various process industries, such as metallurgical industries, food processing industries, concrete mixing industries wastewater treatment industries etc. A conical tank is basically a nonlinear process as its area of cross section varies with respect to level. This paper describes the implementation of PSO based Model Reference Adaptive PI controller for a nonlinear Conical Tank Level System (CTLS). The mathematical model of CTLS is developed and PSO based Model Reference Adaptive (MRA) PI Controller is proposed for this level system. A result of proposed controller is compared with GA based MRA-PI, MRA-PI and conventional PI controllers to analyze the performance in terms of integral square error and Integral absolute error. The results proved that the superiority of proposed controller.